Zeb Store Company Survey: The Effect of Fear of Missing Out (FoMO) and the Role of Social Media Marketing on Customer Satisfaction Moderated by Purchase Decision Variables - Hibatul Azizi, Moch Farhan; Setiawan, Rahyuniati; Lindayani (Li Falah: Journal of Islamic Economics and Business, 2025)
This study examines the combined effects of Fear of Missing Out (FoMO) and social media marketing on customer satisfaction, with purchase decisions serving as a mediating variable. Using a quantitative survey method, data were collected from 269 online shoppers and analyzed through Partial Least Squares Structural Equation Modeling (PLS SEM). The results reveal that both FoMO and social media marketing have significant positive impacts on purchase decisions and customer satisfaction. Moreover, purchase decisions play a crucial mediating role, strengthening the indirect influence of FoMO and social media marketing on satisfaction. The findings contribute to the understanding of digital consumer behavior by integrating psychological and strategic marketing perspectives. Practically, businesses are encouraged to leverage FoMO driven marketing campaigns and optimize social media engagement to enhance customer experience and brand loyalty in the digital marketplace.